THE EFFECT OF INTEGRATIVE LEARNING MODEL TYPE NETWORKED IN LISTENING - Kaharuddin, Kaharuddin (Teaching English as a Foreign Language Overseas Journal, 2022)
The aim of this research is to identify the effectiveness of the Networked Type Integrative Learning Model in Listening for Class VII Students at UPT SMPN 8 Bangkala Barat, Kab. Jeneponto. The researcher was applied pre-experimental design the population is the first-grade students of UPT SMPN 8 Bangkala Barat, Kab. Jeneponto in academic year 2021/2022. In analyzing the numerical data, the writer was used SPSS for windows.  Based on the discussion above, we can conclude that There is an influence of the networked type of integrative learning model on the results of the listening ability of Class VII UPT SMPN 8 Bangkala Barat, Kab. Jeneponto. This can be seen from the research results above that the p-value from the pretest and posttest is lower than ? (0.000<0.05) and the degree of freedom is 22. The t-test value from the pretest and posttest can be concluded that there is a significant difference. This shows that the alternative hypothesis (H1) is accepted and, of course, the null hypothesis (H0) is rejected. This shows that the application of the networked type of integrative learning model to Class VII students at UPT SMPN 8 Bangkala Barat, Kab. Jeneponto can improve students' listening skills